Short Communication: First record of the cassava lace bug Vatiga illudens (Drake, 1922) (Hemiptera: Heteroptera: Tingidae) from East Java, Indonesia - Retno Dyah Puspitarini; Ito Fernando; Yogo Setiawan; Dewi Anggraini; Hammam Abdullah Rizqi (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Puspitarini RD, Fernando I, Setiawan Y, Anggraini D, Rizqi HA. 2021. Short Communication: First record of the cassava lace bug Vatiga illudens (Drake, 1922) (Hemiptera: Heteroptera: Tingidae) from East Java, Indonesia. Biodiversitas 22: 2870-2876. The cassava lace bug, Vatiga illudens (Drake, 1922) (Hemiptera: Heteroptera: Tingidae) is recorded from Indonesia for the first time. This species is found on the abaxial surface of leaves of cassava (Manihot esculenta Crantz, Euphorbiaceae) in several plantations of East Java and heavily infest this plant. Vatiga illudens is native to the Neotropical Region and seems to be the alien species in the Oriental Region. This tingid has already spread over a wide region of East Java, suggesting that the invasion of the lace bug endangers the other regions cultivating cassava.